Blood oxygenation level dependent contrast resting state networks are relevant to functional activity in the neocortical sensorimotor system - De Luca, Marilena; Smith, Stephen; De Stefano, Nicola; Federico, Antonio; Matthews, Paul M. (Experimental brain research, 2005)
The relevance of correlations between blood oxygenation level dependent (BOLD) signal changes across the brain acquired at rest (resting state networks, or RSN) to functional networks was tested using two quantitative criteria: (1) the localisation of major RSN correlation clusters and the task-related maxima defined in BOLD fMRI signal changes from the same subjects; and (2) the relative hemispheric lateralisation (LI) of BOLD fMRI signal changes in sensorimotor cortex. RSN were defined on the basis of signal changes correlated with that of a "seed" voxel in the primary sensorimotor cortex. We found a generally close spatial correspondence between clusters of correlated BOLD signal change in RSN and activation maxima associated with hand movement. Conventional BOLD fMRI during active hand movement showed the expected wide variation in relative hemispheric lateralisation of LI for sensorimotor cortex across the subjects. There was a good correlation between LIs for the active hand movement task and the RSN (r=0.74, p<0.001). The RSN thus define anatomically relevant regions of motor cortex and change with functionally relevant variations in hemispheric lateralisation of sensorimotor cortical interactions with hand movement.